Kelvin-Helmholtz instability-driven magnetopause dynamics as turbulent pathway for the solar wind-magnetosphere coupling and the flank-central plasma sheet communication - Hwang, Kyoung-Joo; Wang, Chih-Ping; Nykyri, Katariina; Hasegawa, Hiroshi; Tapley, Mark B.; Burch, James L.; Fuselier, Stephen A.; Goldstein, Jerry; Dokgo, Kyunghwan; Nakamura, Takuma; Sitnov, Mikhail; Ma, Xuanye; et al. (Frontiers in Astronomy and Space Sciences, 2023)
About sixty years ago Dungey (1961) proposed the solar wind entry and changes in magnetospheric magnetic topology via dayside magnetic reconnection, which initiates the magnetospheric convection over the poles. On the other hand, Axford and Hines (1961) proposed the quasi-viscous interaction via Kelvin-Helmholtz waves/vortices that leads to the solar wind entry and magnetospheric convection. Since then, the two processes have been thought to regulate the solar wind and Earth’s magnetosphere coupling. However, their relative efficiency and importance leave a lot of room for enhanced and quantitative understanding. Kelvin-Helmholtz instability operating on the entire surface of the magnetopause also provide a place for not only solar wind transport but also energetic particle transport or escape, thus, being an efficient channel for two-way transport. Recent observations and simulations indicate that the flanks of the Earth’s magnetosphere can act as a pathway to/from the central magnetotail current sheet. Possible causality between the flank-side dynamics and magnetotail current sheet stability has never been explored. In this paper we discuss our perspective on these unsolved areas of Heliophysics research with brief suggestions of observational and numerical approaches.